2022
DOI: 10.3390/biom12050652
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenomic Changes in Pancreatic Cancer and Their Detection in Stool

Abstract: Pancreatic cancer (PC) is an aggressive malignancy with a dismal prognosis. To improve patient survival, the development of screening methods for early diagnosis is pivotal. Oncogenomic alterations present in tumor tissue are a suitable target for non-invasive screening efforts, as they can be detected in tumor-derived cells, cell-free nucleic acids, and extracellular vesicles, which are present in several body fluids. Since stool is an easily accessible source, which enables convenient and cost-effective samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…Through the modulation of microRNAs (miRNAs), GM and their metabolites significantly influence our epigenome. For instance, the diet–microbiota–miRNAs axis is studied to be associated with the development of colorectal cancer (CRC) 30 . Moreover, it is also correlated with the epigenetic changes for pancreatic cancer, 31 cholangiocarcinoma 32 and biliary tract cancers 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the modulation of microRNAs (miRNAs), GM and their metabolites significantly influence our epigenome. For instance, the diet–microbiota–miRNAs axis is studied to be associated with the development of colorectal cancer (CRC) 30 . Moreover, it is also correlated with the epigenetic changes for pancreatic cancer, 31 cholangiocarcinoma 32 and biliary tract cancers 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the diet-microbiota-miRNAs axis is studied to be associated with the development of colorectal cancer (CRC). 30 Moreover, it is also correlated with the epigenetic changes for pancreatic cancer, 31 cholangiocarcinoma 32 and biliary tract cancers. 33 Although the GM in carcinogenesis such as hepatocellular cancer (HCC) is associated with the immune dysregulation and instability of the host genome, epigenetic changes is a key factor in the progression from inflammation to cancer.…”
Section: Significance Statementmentioning
confidence: 99%
“…Oncogenic mutations in tumor tissues are suitable targets for the noninvasive screening. Numerous efforts have been made to detect tumor-derived cells, cell-free nucleic acids, and extracellular vesicles present in several body fluids, including urine and feces [ 15 ]. Several efforts have been made to develop efficient technology to detect PDAC [ 15 , 16 , 17 ].…”
Section: Diagnosis Through Methods Other Than Dna Sequencingmentioning
confidence: 99%
“…Numerous efforts have been made to detect tumor-derived cells, cell-free nucleic acids, and extracellular vesicles present in several body fluids, including urine and feces [ 15 ]. Several efforts have been made to develop efficient technology to detect PDAC [ 15 , 16 , 17 ]. A recent metagenomics study targeting the gut and oral microbiomes showed that it could provide a powerful source of biomarkers for identifying individuals with PDAC and their prognosis [ 16 ].…”
Section: Diagnosis Through Methods Other Than Dna Sequencingmentioning
confidence: 99%
“…In theory, pancreatic juice with exfoliated cancer or pre-cancerous cells harbouring tumour-specific mutations may be secreted into the intestines and hence be discovered as mutations in the stool. This has indeed been investigated in a few studies, as reviewed by Sammallathi et al, 120 but has yet to make it into clinical practice. Related to this, is the specific microbiome and patterns related to alteration sin healthy compared to patients with cancer.…”
Section: Further Developments and Novel Technologymentioning
confidence: 99%